(untitled) (Value : Jurnal Manajemen dan Akuntansi, 2025)
In an era where business is growing, the discussion about green products should not be forgotten. Not only do they play an important role in the environment, green products also have great potential to become a profitable business. It is important for companies to adopt sustainable and environmentally friendly business practices. Therefore, this study aims to see how Green Brand Image, Green Satisfaction, and Green Trust affect Green Perceived Value towards Green Loyalty on Tupperware products. In this study, a sample of 183 respondents on Tupperware products was involved. Data were processed using Smart-PLS version 4.0.9.9, using a random sampling technique with a purposive sampling technique. The results showed that Green Perceived Value, Green Satisfaction, and Green Trust had a positive influence on Green Loyalty. Green Brand Image also had a positive influence on Green Satisfaction, but was not proven to have an influence on Green Loyalty.